Babes in tomorrowland Walt Disney and the making of the American child, 1930-1960 - Sammond, Nicholas 1960- (Duke University Press, 2005)
Disney makes Disney -- Making a manageable child -- In Middletown -- America's true-life adventure -- Raising the natural child -- Disney maps the frontier